Characterizing Local Interests and Local Knowledge - White, Ryen W. (ACM SIGCHI Conference on Human Factors in Computing Systems (CHI 2012), May 5-10, 2012, Austin, Texas, USA., 2012)
When searching for destinations and activities, the interests and knowledge of locals and non-locals may vary. In this paper, we compare and contrast the search-related interests of these two groups, and when they share a common interest (in our case, for restaurants), we analyze the quality of the venues they intend to visit. We find differences in interests depending on local knowledge, and that locals generally select higher-quality venues than non-locals. These findings have implications for search and recommendation systems that can personalize results based on local knowledge and leverage that knowledge to benefit non-locals.